INVOLVING STUDENTS TO INDEPENDENT LESSONS IN PHYSICAL CULTURE - Voronkov, A.V.; Irkhin, V.N.; Brazhnik, E.A.; Zagoruiko, Yu.A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to substantiate ways to increase the efficiency of attracting university students to independent physical education classes. Methods and structure of the study. Scientific work was carried out in 2020-2021 on the basis of the Belgorod State National Research University. The study used the analysis and generalization of scientific literature, a survey of students, in which 4399 students of the Belgorod State National Research University took part (3212 of them were girls and 1187 boys), an experiment, methods of mathematical statistics. Results and conclusions. As a result of the survey, the reasons for which students do not engage in physical culture were identified. Taking into account the survey data, a system was developed to involve students in independent physical education classes based on the methodology for the integrated development of basic physical qualities, including exercises that do not require sophisticated equipment or visits to fitness centers; the ability to use the means of developing physical qualities that are within the power of a particular student and in which an increase in indicators will invariably be observed, which will ensure the creation of a situation of success; the presence in the information space of video instructions for organizing the process of physical training; the possibility of prompt consultation with specialists (as part of physical education classes, in a group in social networks or in individual contact through social networks); the presence of an incentive system, which includes a set of moral and psychological support of the individual for independent physical education.